Insights Into mRNA and Long Non-coding RNA Profiling RNA Sequencing in Uterus of Chickens With Pink and Blue Eggshell Colors - Chen, Siyu; Chen, Kecheng; Xu, Jiaming; Li, Fangwei; Ding, Jinlong; Ma, Zheng; Li, Gen; Li, Hua (Frontiers in Veterinary Science, 2021)
The blue egg is both of biological interest and economic importance for consumers, egg retailers and scientists. Up to date, the genetic mechanisms underlying pigment have mainly focused on protein-coding genes. However, the underpinning mechanism of non-coding RNAs on the pigment deposition among different eggshell colors remain unknown. In this study, RNA sequencing was employed to profile the uterine gland transcriptome (lncRNA and mRNA) of 15 Changshun blue eggshell layers, to better understand the genetic mechanisms of deposition of blue eggshell color. Results showed that differentially expressed mRNAs, GO terms and KEGG pathways among pink-eggshell and blue eggshell chickens were mainly targeting immune and transporter-related terms with the SLC family, IgJ, CD family, and MTMR genes. Further, the progesterone-mediated oocyte maturation and cortisol synthesis and secretion pathway with targeted gene PGR and Pbx1 were significantly enriched between blue and pink eggshell chickens. Integrating analysis of lncRNA and mRNA profiles predicted 4 and 25 lncRNA-gene pairs by antisense and cis analysis. They were relative to immune, nerve, and lipids and amino acid metabolisms, porphyrin and chlorophyll metabolism with targeted gens FECH and oxidative phosphorylation and cardiac muscle contraction pathways with targeted gene COX6A1. Within blue eggshell chickens, the GO term hindbrain tangential cell migration and phosphatidylinositol monophosphate phosphatase activity with targeted gene Plxna2, and MTRM1 were identified. Integrating analysis of lncRNA and mRNA profiles predicted 8 and 22 lncRNA-gene pairs. Most pathways were mainly enriched on lipid-related metabolisms as found in mRNA sequencing. The lncRNAs did exert similar functions in color formation by modulating pigment disposition, immune and lipid related metabolisms. Our results provide a catalog of chicken uterine lncRNAs and genes worthy of further studies to understand their roles in the selection for blue eggshell color layers.